2014
DOI: 10.1088/1475-7516/2014/09/043
|View full text |Cite
|
Sign up to set email alerts
|

Star-forming galaxies as the origin of diffuse high-energy backgrounds: gamma-ray and neutrino connections, and implications for starburst history

Abstract: Abstract. Star-forming galaxies have been predicted to contribute considerably to the diffuse gamma-ray background as they are guaranteed reservoirs of cosmic rays. Assuming that the hadronic interactions responsible for high-energy gamma rays also produce highenergy neutrinos and that O(100) PeV cosmic rays can be produced and confined in starburst galaxies, we here discuss the possibility that star-forming galaxies are also the main sources of the high-energy neutrinos observed by the IceCube experiment. Fir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
323
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 262 publications
(338 citation statements)
references
References 154 publications
(321 reference statements)
14
323
0
1
Order By: Relevance
“…Since the superclusters are likely to be much more frequent in starburst galaxies CRs escaped from these accelerators may support a diffuse CR population with spectral slope harder than that observed in the Milky Way and consistent with that derived Fig. 2 The gamma-ray spectra of starburst galaxies M82, NGC 253, NGC 1068 and others detected by the Large Area Telescope aboard Fermi observatory and imaging atmospheric Cherenkov telescopes adopted from Ackermann et al (2012) by Tamborra et al (2014). Other possible PeV neutrino sources were proposed recently including semirelativistic hypernova remnants by Liu et al (2014) and shock acceleration of PeV CR particles in massive galaxy mergers or collisions by Kashiyama and Mészáros (2014).…”
Section: Supernovae In Starburst Regionssupporting
confidence: 70%
See 1 more Smart Citation
“…Since the superclusters are likely to be much more frequent in starburst galaxies CRs escaped from these accelerators may support a diffuse CR population with spectral slope harder than that observed in the Milky Way and consistent with that derived Fig. 2 The gamma-ray spectra of starburst galaxies M82, NGC 253, NGC 1068 and others detected by the Large Area Telescope aboard Fermi observatory and imaging atmospheric Cherenkov telescopes adopted from Ackermann et al (2012) by Tamborra et al (2014). Other possible PeV neutrino sources were proposed recently including semirelativistic hypernova remnants by Liu et al (2014) and shock acceleration of PeV CR particles in massive galaxy mergers or collisions by Kashiyama and Mészáros (2014).…”
Section: Supernovae In Starburst Regionssupporting
confidence: 70%
“…Recent modeling by Tamborra et al (2014) suggested that starbursts, including those with active galactic nuclei and galaxy mergers, could be the main sources of the high-energy neutrinos observed by the IceCube Observatory (see also Anchordoqui et al (2014)). Assuming a cosmic-ray spectral index of the diffuse CR population to be 2.1-2.2 for all starburst-like galaxies and extrapolating from GeV to PeV energies the authors obtained fluxes consistent with both the Fermi and IceCube data.…”
Section: Supernovae In Starburst Regionsmentioning
confidence: 99%
“…In other words, the number i of high flux sources in a pixel is drawn from the Poisson distribution P (i|k ). This is reflected by the binomial expansion: for 1 (which also implies k i) we have 6) such that (reassembling all the elements of the discussion above)…”
Section: B2 Deriving the Form Of P K (F )mentioning
confidence: 98%
“…Components contributing to this background include blazars [4,5], star-forming and starburst galaxies [6], and misaligned active galaxies [7]. The combination of these sources gives reasonably good fit to the spectral data [5,8], while the anisotropies are consistent with the blazar component alone [3,9].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation